Comparative Study between Romania and Visegrad Countries, Related to Agricultural Sector Performance - Ira A. SIMIONOV; Alina MOGODAN; Stefan M. PETREA; Aurelia NICA; Dragos S. CRISTEA; Sarina ROSENBERG; Victor CRISTEA (Communications of International Proceedings, 2020)
The purpose of the present study is to compare the dynamics of 6 agricultural parameters (crop yield, employment rate, total GVA, the GVA of the agriculture sector, DP and LPA) in Romania and the countries within the Visegrad Group, between the years 2007-2013.Poland registered the highest GVA, GVA from agriculture and DP between the years 2007 and 2013. Romania scored the highest percentage of the employment rate between the studied timeline. Czech Republic registered the highest crop yield and LPA. Continuous monitoring of the European agriculture performance is needed in order to identify a long-term trend and develop prediction models, for future development of support strategies and legislation framework of the sector.
Keywords: Agricultural sector performance; crop yield; employment rate; Visegrad Group.